(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2011)
This paper explores the possible restoration of a leadership role for the humanities in university-based knowledge building and education. Such a global restoration is required in the face of various social, ethical, and human capital dilemmas associated with such issues as climate change, financial market instability, and the exclusion of many people from a privileged, 'high-tech' knowledge society. Although traditional humanities faculties in Western universities have long been in decline, many emerging 'technological' universities in Asia still view a knowledge of the humanities as a prerequisite to and indicator of maturity and a well-rounded education. This paper will investigate the potential roles and interests of re-invigorated humanities disciplines in terms of (a) the formal enterprise of human knowledge building both inside and outside of the Academy and (b) their particular relevance to an Asia-Pacific context as well as to an interconnected, global network society. The paper develops two related proposals. The first proposal is that we might rescue from the 'ruins' of the arguably discredited Western humanities project a more globally convergent foundation for the humanities. We develop this distinction by deploying the universal insights and enduring contributions of two of the most brilliant and perhaps wisest inheritors of the humanities project in the West, Paul Ricoeur and Hannah Arendt. The second proposal that we explore holds that, because emerging Asian universities are not so deeply stuck in the West's out-of-date categories and framework, they may be in a better position to help reinvent the humanities in terms of 21st century possibilities and imperatives that are grounded in the local contexts of the global knowledge-building convergence.